Towards Personalization in the Curative Treatment of Gastric Cancer - Slagter, Astrid E.; Vollebergh, Marieke A.; Jansen, Edwin P. M.; van Sandick, Johanna W.; Cats, Annemieke; van Grieken, Nicole C. T.; Verheij, Marcel (Frontiers in Oncology, 2020)
Gastric cancer is the fifth most common cancer worldwide and has a high mortality rate. In the last decades, treatment strategy has shifted from an exclusive surgical approach to a multidisciplinary strategy. Treatment options for patients with resectable gastric cancer as recommended by different worldwide guidelines, include perioperative chemotherapy, pre-or postoperative chemoradiotherapy and postoperative chemotherapy. Although gastric cancer is a heterogeneous disease with respect to patient-, tumor, and molecular characteristics, the current standard of care is still according to a one-size-fits-all approach. In this review we discuss the background of the different treatment strategies in resectable gastric cancer including the current standard, the specific role of radiotherapy, and describe the current areas of research and potential strategies for personalization of therapy.